Biotechnological Applications of Manganese Peroxidases for Sustainable Management - Kumar, Ashish; Arora, Pankaj Kumar (Frontiers in Environmental Science, 2022)
Microbial manganese peroxidases (MnPs) are ligninolytic enzymes primarily responsible for degrading lignin, but they are also capable of degrading dyes, organic pollutants, and emerging contaminants in wastewater They have been isolated and characterized from many white-rot fungi and few bacteria. For microbial MnPs, the optimum pH range is between 3.5 and 9.0; the optimum temperature range is between 25 and 70 °C. Their molecular weights range between 25 kDa and 68 kDa. By oxidizing Mn2+ to Mn3+, they can oxidize a wide range of phenolic and non-phenolic substrates. MnPs can be used in a wide range of industrial applications, including delignification of pulp, wastewater treatment, biofuel production, dye removal, biopulping, biobleaching, and juice extract clarification. The purpose of this review is to summarize biotechnological applications of manganese peroxidases.